Crime and the multi-ethnic society: a view from Europe - Bovenkerk, Frank (Crime, law and social change, 1993)
The old questions about possible relationships between "race" or ethnicity and crime are shown to be unsatisfactory as they have been based on the wrong assumption that race and ethnic background constitute natural categories. The author discusses recent crime patterns in Europe - and in The Netherlands in particular - that have emerged as a result of societies becoming multiethnic. His research agenda includes the study of contrasting crime profiles, patterns of police selectivity, discrimination and racist violence, culture conflict and internationally organized crime.